Prognostic impact of peripheral blood Wilms' tumour 1 mRNA expression levels in response to azacytidine in MDS: A single-centre analysis. (2021) - Maeda, Tomoya; Matsuda, Akira; Asou, Chie; Okamura, Daisuke; Tanae, Ken; Kohri, Mika; Ishikawa, Maho; Takahashi, Naoki; Tsukasaki, Kunihiro; Kawai, Nobutaka; Asou, Norio; Bessho, Masami
Abstract: To determine the impact of peripheral blood (PB) Wilms' tumour 1 ( WT-1 ) mRNA levels in patients with primary myelodysplastic syndromes (MDS), we analysed the relationships between several clinical variables at the time of diagnosis and the haematological response of patients treated with azacytidine. We observed overall responses in 20 (63%) patients; there were no significant differences in clinical variables, including bone marrow blast counts, IPSS scores and IPSS-R risk scores, between responders and non-responders. The responders' PB WT-1 mRNA levels were significantly lower than those of non-responders ( P  = 0.03). PB WT-1 mRNA expression could be a marker for predicting the response to azacytidine in patients with de novo MDS.